Pengaruh Profitabilitas Dan Leverage Terhadap Manajemen Laba Dengan Eksekutif Wanita Sebagai Variabel Moderasi - Eny Purwaningsih; Melinda Mayangsari (CERED Indonesia Institute, 2023)
and female executives on earnings management either partially or simultaneously in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2020 period. This study uses a type of causal research. The sample in this study is the food and beverage sub-sector at manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period using the purposive sampling method. There are 10 companies that meet the criteria of the research sample, so the sample is 50 financial statements. The results showed that there was a simultaneous influence of profitability (NPM) and leverage (DER) variables on earnings management which was moderated by female executives (EW). The results show that partially there is an effect of the profitability variable (NPM) having a negative effect on earnings management and female executives (EW) can weaken the influence of profitability (NPM) on earnings management, while the leverage variable (DER) has no effect on earnings management and executives women cannot moderate the effect of leverage (DER) on earnings management.